Medium: Wizualizacja pierwszej warstwy narracyjnej: Odkrywanie - Koprowicz, Jacek (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2012)
The Film Medium. Visualization of the First Layer of the Narrative Level: Discovery A director’s analysis of the narrative layers in the film Medium allows one see, among other things, the construction of individual elements of the film. Through an analysis of the construction of particular scenes and the relations between them within the story, the text describes the visual narrative structure of the first layer, i.e. “discovery” (the next layers are: confirmation, confrontation and fulfillment). Within the horror genre, this layer is an essential element in building a dramaturgical structure and in influencing the viewers’ reactions (including the visual pleasure of “discovering”).